Oral Health Knowledge, Attitude and Practices among Adults toward Tooth Loss and Utilization of Dental Services in Moradabad District - Yadav, Vipul; Tandon, Vaibhav; Pal, Sumit; Ravishankar, TL; Kaur, Harsimran; Moudgil, Munmun (Journal of Orofacial Research, 2012)
Background and objectives: For centuries, people have accepted tooth loss as an inevitable part of the human condition. Tooth loss impairs the quality of life, often substantially, and affects the well being of the person. The objectives of study were to evaluate behavioral characteristics of the adults like beliefs about tooth loss and utilization of available health services which might be associated with tooth loss. Methodology: A cross-sectional survey was conducted on 1,200 adults of Moradabad district, aged 35 to 74 years, 565 from urban area and 635 from rural area who were selected by multistage systematic random sampling technique. Data was collected by an interview followed by examination for the number of missing teeth. Results: Mean number of missing teeth in the study population was 4.2. Around half of the study population, i.e. 51.1% of the adults claimed that they had no dental treatment facilities nearby. Among the 602 adults (50.2%) who had utilized dental services earlier, greatest response for reason of dental visit was for extraction of teeth (48.7%). Conclusion: The findings from this study are useful in identifying the sociodemographic and behavioral characteristics associated with tooth loss among the study population. The insights gained from this study illustrate the need for tailoring Oral Health Promotion Programs and Services for the community, as the modification of these nondisease independent factors can reduce the tooth loss and improve the oral health of the adults of Moradabad district.